Identifying the factors affecting the growth of the employees of the country's property and documents registration organization - Najmeh Ahmadi; Kolsoum Nami; Nader Ghourchian; Parivash Jafari (مدیریت و چشم انداز آموزش)
Abstract The purpose of the current research is to identify the factors affecting the growth of the employees of the country's property and document registration organization. The research method is applicable in terms of purpose, and qualitative in terms of its implementation. The statistical population of this research included 15 experts in the field of employee growth and development. The sampling method is purposeful. A semi-structured interview was used to collect information. Data analysis was done using open and axial coding method. The results showed that two general categories of components were identified. Individual growth includes scientific background, responsibility, and professional commitment; and organizational growth includes livelihood, management, codified and comprehensive educational program, motivational programs, career evaluation and promotion system, improvement and modernization of human resources and work environment, comprehensive program of updating and improvement of work processes, and mental health of the work environment. Factors, indicators and the final research model were designed based on the results of the qualitative interview. The designed model can be the basis for better decision-making and managers' planning to enhance the growth of employees. Extended abstract Introduction The main factor determining the growth of the society in the current changing conditions of the world is the availability of efficient and creative human resources, which depends on the availability of knowledge, education, and research. The superiority of a country depends on the degree of benefit of that country from science and technology, which is the result of scientific development, rather than relying on natural resources (Abdollahi et al, 2022). The development of employees means the formation of all the capacities necessary in learning knowledge, information, and specialized professions in human resources; to enable them to create a position of quality and value-creating services in the organization, and perform optimally the duties and responsibilities that they are committed to in the organization, associated with efficiency and effectiveness (Doroudi & Kangeroudi, 2014). Therefore, the growth of employees plays an important role in the success of organizations; and today, without a doubt, what distinguishes successful, developed and advanced organizations and companies from others is their human resources. Today, human resources is the only resource with a high impact factor, the enrichment of which creates significant added value for the organization, and the modern and scientific management of employee performance can provide the grounds for organizational growth and employee growth, and contribute significantly to create and maintain a competitive advantage, the desired improvement and transformation of the organization, and the realization of the organizational performance (Nowrozi Fard & Zamani, 2016). Based on this, the current research is looking for an answer to this question: What are the factors affecting the growth of the employees of the country's property and document registration organization? Theoretical Framework Organizational growth and employees Growth means planned efforts to create and produce some kind of transformations, the purpose of which is to help all the personnel of organizations to have the ability and power to do the work they are responsible for in a more efficient and effective way than before. It should be said that growth is a tool for updating departments and information, and rapid development and expansion of the organization (Sobhani et al, 2018). Organizational growth is an informed and planned science of change jointly by managers, change specialists, and employees to solve problems. At the heart of this action is change; achieving organizational efficiency with an emphasis on humanity and popular principles. In other words, organizational growth focuses on human behavior. Mainly, organizational growth is ensuring the organization achieves its goals through improvement of individual and group performance (Karakaya & Yelmaz, 2016). Personal growth is an individual and internal thing, where personal factors and priorities are the most important (Seyed Hatami et al, 2023). Through the personal growth, the employees begin to create a friendly relationship with colleagues, participation and interaction with them; also help their colleagues and their health and well-being, and try to establish a friendly relationship with organizational managers and raise the threshold of their work tolerance; but in the dimension of professional growth, they often focus on the place of activities of service, education, learning, and professional growth. In order to achieve growth and development in this dimension, personnel are more interested in studying and increasing their scientific knowledge, and become members in Organizational teams and participate in training, specialized, and in-service courses (Rezaian et al, 2014). Seyed Hatami et al, (2023) in a research conducted with the aim of compiling the growth pattern of faculty members at Farhangian University, used semi-structured interviews to collect data. The research findings of these researchers showed that the basic categories of growth are based on antecedents, processes and outcomes. The results of the research emphasized on the attention to the extractive categories of the model in university policy making. Jabbarimaraghosh et al, (2022) concluded from their research that there is a positive and meaningful relationship between spiritual leadership and entrepreneurship and growth; and according to the research findings, the effect of spiritual leadership on growth is 0.37. The above research is of descriptive type, and correlative in terms of method, of causal modeling type. Research methodology The research method is applicable in terms of purpose, and qualitative in terms of its implementation. The statistical population of this research included 15 experts in the field of employee growth and development. The sampling method is purposeful. A semi-structured interview was used to collect information. Research findings Data analysis was done using open and axial coding method. The results showed that two general categories of components were identified. Individual growth includes scientific background, responsibility, and professional commitment; and organizational growth includes livelihood, management, codified and comprehensive educational program, motivational programs, career evaluation and promotion system, improvement and modernization of human resources and work environment, comprehensive program of updating and improvement of work processes, and mental health of the work environment. Factors, indicators and the final research model were designed based on the results of the qualitative interview. The designed model can be the basis for better decision-making and managers' planning to enhance the growth of employees. Conclusion The current research was conducted with the aim of identifying the factors affecting the growth of the employees of the country's property and document registration organization. The results of this research are in agreement with the results of Seyed Hatami et al, (2023), jabbarimaraghosh et al, (2022), Abdollahi et al, (2022), Younessi et al, (2022), Kanjanakan et al, (2023), Saberi Nasrabad Sefali et al, (2022), Oncioiu Ionica et al, (2021), Hejazi (2020), Mohammadkhani et al, (2019), Shabani bahar et al, (2020), and Hosseini Kuhsari et al, (2021). Saberi Nasrabad Sefali et al, (2022) showed that the components of employee growth (leadership actions, employee participation, accessibility, and training of employees and learning capacity) have a positive and significant relationship with employee productivity; therefore, the management of the university should make more efforts and activities to increase the productivity of the employees in order to improve the growth components of the employees. According to the identification of the components of employee growth in this research, in order to facilitate and provide the conditions for employee growth, it is suggested to pay special attention to the salaries and wages and improve the livelihood of employees; to use the management raised from among the employees who have sufficient mastery and knowledge of the organization; to use training methods appropriate to the organization of documents and real estate registration; needs assessment and motivational programs should be designed in order to strengthen the motivation of employees; equal opportunities for promotion and fair evaluation of employee performance should be carried out; recruiting and maintaining human resources should be expertized; information technology should be used to improve work processes; legal and lawful support programs should be designed for employees; recruitment of employees should be based on specialized interviews; employees with morals should be appreciated materially and spiritually; and establishment of direct and reciprocal communication between employees and managers is suggested.